2007
DOI: 10.1110/ps.062608807
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of the binding of monomeric and dimeric ephrins to Eph receptors: Correlation to function in a growth cone collapse assay

Abstract: Eph receptors and ephrins play important roles in regulating cell migration and positioning during both normal and oncogenic tissue development. Using a surface plasma resonance (SPR) biosensor, we examined the binding kinetics of representative monomeric and dimeric ephrins to their corresponding Eph receptors and correlated the apparent binding affinity with their functional activity in a neuronal growth cone collapse assay. Our results indicate that the Eph receptor binding of dimeric ephrins, formed throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 22 publications
7
37
0
Order By: Relevance
“…Avidity effects are strongly dependent on the valency of the ligand, as observed, for example, with binding of dimeric ephrin-A5 ligand to dimerized EphA3 receptor (45). Accordingly, the measured K d values for FKs to our CD46ex-Fc were about 5 logs lower for the Ad3/7-FKs and 3 logs lower for Ad11/35-FKs compared to the K d values for the monovalent CD46-SCR I-II interactions published by others (10,47,48,71,72).…”
Section: Discussionsupporting
confidence: 46%
“…Avidity effects are strongly dependent on the valency of the ligand, as observed, for example, with binding of dimeric ephrin-A5 ligand to dimerized EphA3 receptor (45). Accordingly, the measured K d values for FKs to our CD46ex-Fc were about 5 logs lower for the Ad3/7-FKs and 3 logs lower for Ad11/35-FKs compared to the K d values for the monovalent CD46-SCR I-II interactions published by others (10,47,48,71,72).…”
Section: Discussionsupporting
confidence: 46%
“…Recently our studies have demonstrated that fluorescently labeled TM fragments of the EphA1 receptor self-associate in liposomes, forming helical dimers crossing the lipid bilayer (19). Consistent with this notion and with the fact that Eph-ephrin signaling requires lateral dimerization or aggregation in cell membrane (2,6,12,20), we present the high resolution spatial structure of the homodimeric TM domain of the human EphA1 receptor obtained by heteronuclear NMR in lipid bicelles combined with molecular dynamics (MD) relaxation in explicit membrane. The found dimerization specificity and dependence of structural-dynamic properties of the EphA1 TM domain on ionization state of the membrane embedded glutamate carboxyl group tempted us to speculate how extracellular conditions and local cell membrane environment can modulate biological activity of the receptor, providing a better understanding of the molecular mechanism of the Eph-ephrin signaling.…”
supporting
confidence: 55%
“…It should be noted that Fc fusion proteins are dimeric, which increases their binding avidity. 23,24 Nevertheless, the apparent K D values obtained with this method can be used to compare the binding strengths of different Eph receptor-ephrin combinations.…”
Section: Resultsmentioning
confidence: 99%